ATTITUDES OF SPORTS FANS IN MONTENEGRO TOWARD NATIONAL IDENTITY AMONG THE FREQUENCY OF THEIR PARTICIPATION IN SPORT ACTIVITIES - Stevo Popović; Duško Bjelica; Ivan Vasiljević; Rašid Hadžić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2014)
Introduction: Sport and national identity have been strongly connected through entire history, mostly due to the reason that an individual sportsmen or a national sport team may represent a certain group of people united around a single goal or the same ideas (Popović & Bjelica, 2013). Hence, they, accompanied with the sports fans, represent an entire nation and foster a sense of national pride amongst members of a given nation (Bogdanov, 2011). Consequently, this research was aimed at gaining relevant knowledge about the attitudes of sports fans that constantly attend the matches of national team toward national identity, mostly due to the reason the authors of this research believed that it could vary according to the frequency of their participation in sport activities in a month. Methods: The sample included 669 respondents who participate in sport activities more than 20 times (n=165), 11-20 times (n=98), 5-10 times (n=130), 1-4 times (n=108), less than ones a month (n=71) and as well as sports fans who never participate (n=97). The sample of variables consisted of 19 items, and the subjects were evaluated it by a seven-point Likert scale. Regarding the statistical analysis, descriptive statistics and Two-sample Hotelling's T-Square test were employed. Results: Based on the results it was concluded that significant differences occurred between sport fans who participate in sport activities more than 20 times (M±SD=4.52±1.51) and those who have never participated it (M±SD=4.26±1.50), those who participated less than ones (M±SD=4.29±1.53) and those who participate 1-4 times a month (M±SD=4.37±1.38), as well as between sport fans who participate in sport activities 11-20 times (M±SD=4.46±1.35) and those who have never participated it and those who participate it less than ones a month. Discussion: Sport is well positioned when we talk about the development of national identity, due to the reason there are many evidence from the previous literature (cited in Popović and Bjelica, 2013) that achievements of national sports teams and organization of major sports events can increase it. In addition, this study recognized stronger affiliation of the subjects who participate in sport activities more to the nation. Although sport is not only one factor that can influence national identity, the results of this study suggest that the personal involvement of sports fans in sports activities might also strengthen its self-esteem and national pride. References: Popović S, Bjelica D (2013). Sport Mont, 37-39, 61-66. Bogdanov D (2011). Influence of National Sport Team Identity on National Identity. Unpublished Doctoral Dissertation. Tallahassee, FL: The Florida State University.